CIVIL-MILITARY COOPERATION AND GENDER PERSPECTIVES: EUROPEAN AND UKRAINIAN REALITIES - Titko, Elvira; Kurovska, Ilona; Korniienko, Petro; Balzhyk, Irena A.; Stoyatska, Ganna M. (Revista Direito e Sexualidade, 2023)
The article is primarily aimed at studying and analysing social relations, roles, and dynamics in the field of civil-military cooperation and gender policy. The authors analyze various social stereotypes, political decisions, legislation, and its impact on gender equality and interaction between civil society and the military. In turn, empirical data is used to confirm or refute hypotheses about gender imbalances, challenges and achievements in these areas, but this research is focused on social analysis and understanding of current challenges in the chosen field. The research presupposed the use of various scientific methods, but its base was formed by general and special scientific and philosophical methods. Particular emphasis was placed on the formal-legal approach that facilitated in-depth analysis of international legal statutes, doctrinal perspectives, and rulings from the European Court of Human Rights concerning gender policies embedded within the framework of civil-military cooperation. The authors conduct a theoretical legal examination of civil-military cooperation within the framework of human rights defense, elucidating its distinctive features. Additionally, the paper places considerable emphasis on gender equality in the context of armed conflicts and civil-military cooperation, drawing upon international legal perspectives and scholarly methodologies.